The evolution of inequality aversion in a simplified game of life - Stephan Müller (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper applies the indirect evolutionary approach to study the evolution of inequality aversion in a simplified game of life. The game comprises a dilemma, a problem of coordination, and a problem of distribution as a general framework for the evolution of preferences. In singlegame environments, there emerges a global advantage for inequality-averse individuals in the dilemma and a global disadvantage for inequality-averse players who are favoured by the problem of distribution. The simplified game of life puts these strong predictions into perspective. In particular, selfish and inequality-averse individuals may coexist in the subpopulation, favoured in the problem of distribution.
Keywords: C72; C73; 330; inequality aversion; evolution; preferences